VP159 Strengthening Primary Health Care In Nigeria By Patient Involvement. (12th January 2018) - Ekpenyong, Aniekan; Adeyemi, Sylvester
Abstract : INTRODUCTION: The Health system in Nigeria is structured into three tiers which include tertiary health care, secondary health care and primary health care (PHC). The latter forms the grassroots system of delivering basic health services to communities in both rural and urban centers. However PHC in Nigeria have been affected by poor service delivery. This has resulted in underuse of PHC due to the acceptance and utilization of health services delivered through this system. This research seek to bridge the gap of inequality, reaffirm that implementing PHC is a human right/duty and fosters patient and consumer involvement for economic, social and environmental sustainability of PHC. METHODS: A qualitative method of research was adopted using a participatory research model. The relative data was sourced secondarily from recent findings (July 2015) carried out in seventy-three primary health centers across Anambra State, Benue State, Kaduna State, Plateau State and Federal Capital Territory (FCT) of Nigeria. Issues that were examined included: client perspective and community involvement, status of available services, utilization and service delivery, and infrastructure and human resource capacities. The respondent of 294 client/service user population from interview were recorded and analyzed. RESULTS: The assessment showed client dissatisfaction to services being provided. In most centers, National Primary Health Care Development Agency (NPHCDA) requirements like availability of basic functional equipment, well trained health workers, patient record system, and access to water and sanitation were not met. Most of the facilities visited reported to be disconnected from the health system due to supportive supervision. CONCLUSIONS: Conclusively, the interest of the underserved Nigerian could be advocated for through local committees of consumer organizations. Their involvement will have an impact in PHC evaluation, policy making, and implementation of action plans aimed at improving PHC services.